'Hearing silences': Exploring culturally safe transitional care: A qualitative study among Turkish-speaking migrant frail older adults - Dolu, İlknur; Hayter, Mark; Serrant, Laura; Lee, Amanda; Dolu, İlknur (Wiley, 2024)
Aims: This study aimed to investigate the experiences and transitional care needs of Turkish frail older adults living in the UK and determine how this information can be utilized to improve the provision of culturally sensitive care during the transitional period.Design: Qualitative descriptive research with semi-structured individual interviews.MethodsThe 'Silences' Framework guided the research design, from conceptualizing the research question to structuring the report of final outputs. For this study, semi-structured, in-depth interviews were conducted with sixteen older adults living with frailty and five family caregivers between January and May of 2023 in the United Kingdom.Results: Major themes that were identified included: (i) information and communication, (ii) care and support, (iii) the role of culture and (iv) trust and satisfaction. Further analysis, through discussion and immersion in the data, revealed that care transition periods were presented alongside three phases of transitional care: pre-transition (during hospitalization), early-transition (the period between discharge and the 7th day after discharge) and late transition (the period between the 8th day and 12th month after discharge).Conclusions: Our study revealed that the communication and informational needs of frail older individuals change during the transition period. While Turkish older adults and family caregivers expressed satisfaction with healthcare services in the UK, many struggled due to a lack of knowledge on how to access them.Impact: The support of family caregivers is a crucial component in facilitating transitional care for frail older patients, as they help in accessing healthcare services and using technological devices or platforms. It should be noted that family caregivers often hold the same level of authority as their elderly Turkish counterparts.Patient or Public Contribution: No patient or public contribution.
Keywords: Care; Cultural Issues; Diversity And Inclusion In Healthcare; Ethnicity; Older People